Petroleum geology controlled by extensive detachment thinning of continental margin crust: A case study of Baiyun sag in the deep-water area of northern South China Sea - PANG, Xiong; REN, Jianye; ZHENG, Jinyun; LIU, Jun; YU, Peng; LIU, Baojun (Petroleum exploration and development, 2018)
The relationships between crustal stretching and thinning, basin structure and petroleum geology in Baiyun deep-water area were analyzed using large area 3D seismic, gravity, magnetic, ocean bottom seismic (OBS), deep-water exploration wells and integrated ocean drilling program (IODP). During the early syn-rifting period, deep-water area was a half-graben controlled by high angle faults influenced by the brittle extension of upper crust. In the mid syn-rifting period, this area was a broad-deep fault depression controlled by detachment faults undergone brittle-ductile deformation and differentiated extension in the crust. In the late syn-rifting period, this area experienced fault-sag transition due to saucer-shaped rheology change dominated by crustal ductile deformation. A broad-deep fault depression controlled by the large detachment faults penetrating through the crust is an important feature of deep-water basin. The study suggests that the broad-deep Baiyun sag provides great accommodation space for the development of massive deltaic-lacustrine deposition system and hydrocarbon source rocks. The differentiated lithospheric thinning also resulted in the different thermal subsidence during post-rifting period, and then controlled the development of continental shelf break and deep-water reservoir sedimentary environment. The high heat flow background caused by the strong thinning of lithosphere and the rise of mantle source resulted in particularities in the reservoir diagenesis, hydrocarbon generation process and accumulation of deep-water area in northern South China Sea.